Navigating Merdeka curriculum in first grade: teacher challenges and strategies - Salati Asmahasanah; Irma Cintya Chairunnissa; Nurman Hakim (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2023)
This study investigates the difficulties encountered by first-grade teachers in implementing the Merdeka Curriculum and analyzes the techniques used to overcome these obstacles. A qualitative research methodology with a descriptive approach was utilized to gather data via observation, interviews, and documentation, followed by a thorough analysis of data reduction, presentation, and conclusion drawing. The findings reveal various challenges, including the lack of familiarity with the new terminology for learning outcomes, objectives, lesson plans, and modules related to the Pancasila Student Profile Strengthening Project (P5). Furthermore, students demonstrate inadequate preparation for the Pancasila Student Profile Project. Educators respond by seeking official information on the Merdeka Curriculum through Ministry of Education and Culture resources, participating in relevant webinars, discussing with colleagues, and embracing new pedagogical approaches and media. Additionally, collaboration with students and parents is emphasized for the productive implementation of lesson plans and project modules. This study suggests implementing ongoing support mechanisms such as continuous training and resource sharing to improve teachers' competencies in implementing Merdeka Curriculum effectively in first grade.